2019
DOI: 10.1002/em.22348
|View full text |Cite
|
Sign up to set email alerts
|

The potential application of human PIG‐A assay on azathioprine‐treated inflammatory bowel disease patients

Abstract: The rodent Pig-a assay has been used extensively as a potential regulatory assay for evaluating the in vivo mutagenicity of test substances. Although the assay can be conducted in different mammalian species, there have been only a few reports describing its use in humans, and rarely in genotoxicant-exposed human populations. In this study, PIG-A mutation frequencies (MFs) were evaluated in 36 azathioprine (AZA; human carcinogen)-treated inflammatory bowel disease (IBD) patients and 36 healthy volunteers. IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Recently, Cao et al (2020) reported a slight increase in mutant phenotype erythrocytes in Chinese IBD patients. Two differences between these studies are noteworthy, and one is related to methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Cao et al (2020) reported a slight increase in mutant phenotype erythrocytes in Chinese IBD patients. Two differences between these studies are noteworthy, and one is related to methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Since genomic damage is recognized as playing a key role in the multistep process of carcinogenesis, this work suggested that IBD itself (at least in several mouse models) may be responsible for some portion of the elevated risk of hematopoietic cancers. More recently, Cao et al (2020) extended the study of genotoxicity biomarkers from laboratory rodent models to IBD patients in China. They found that adult IBD patients exhibited markedly higher micronucleated lymphocyte frequencies compared to an age-matched healthy adult population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This laboratory and others have previously reported significant progress adapting these rodent assays to human blood analyses (Dertinger et al ., 2004, 2007, 2015; Grawé et al ., 2005; Offer et al ., 2005; Witt et al ., 2007; Dobrovolsky et al ., 2011; Cao et al ., 2016, 2020a, 2020b; Horibata et al ., 2016; Khattab et al ., 2017; Haboubi et al ., 2019). Here, we report methodological improvements that overcome barriers to wide‐spread use.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, genetic toxicology tests and methods of human gene mutation detection were not suitable for human biomonitoring studies. However, in the last months, PIG‐A gene mutation has been used as a genotoxicity biomarker in various exposure scenarios in humans, in combination with the formation of micronuclei (Cao et al ., 2020a, 2020b). Moreover, optimized protocols related to human blood PIG‐A mutation and micronucleated reticulocyte flow cytometric assays have been published (Torous et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%